Adolescents’ Vulnerability to Fake News and to Racial Hoaxes: A Qualitative Analysis on Italian Sample - Concetta Papapicco; Isabella Lamanna; Francesca D’Errico (Multimodal Technologies and Interaction, 2022)
Following the Digital Revolution, we are witnessing an increase in the number of manipulated sources of information. For this reason, virtual environments can be a breeding ground for the proliferation of prejudices and stereotypes, resulting from the spread of racial fallacious news, known as ‘racial hoaxes’. Adolescents may be more susceptible due to the tense and complicated relationship between their experience with digital platforms and the development of their relatively limited critical thinking. In this landscape, in order to explore the features of disinformation in adolescence, the research involved 41 Italian adolescents between 13 and 16 years old, balanced by gender and school education. The teenagers took part in the focus group discussions on the topic of online information preferences, fake news and racial hoaxes, which were analyzed by means of content analysis. The answers given by participants show a so-called adolescents’ perception of ‘misinformation invulnerability’ that can influence their credulity in fake news, since they are aware of fake news but they are not so able to recognize or remember it.